News shocks modeling on monetary policies using dynamic stochastic general equilibrium (DSGE) model: Case analysis. Issue 4 (14th October 2019) - Zarei, Shapoor; Marzban, Hussain; Samadi, Ali H.; Javaheri, Ahmad Sadraei
Abstract : Purpose: The purpose of this paper is to investigate the effects of news shocks on monetary policies using the dynamic stochastic general equilibrium (DSGE) model. To this end, two kinds of news shocks (known as technology and consumer preferences) are defined according to Khan and Tsoukalas' (2012) approach. Design/methodology/approach: In order to construct and simulate the DSGE model to approaching the real conditions in a case study, consumption habits in the utility function were concerned based on the assumption of the zero-value obtained from multiplying the inflation by the real interest rate in the Fisher's equation, whereas the real interest rates in the long run were appointed as negative remark in simulating the monetary policy models. The estimation and simulation results for the research models indicated that monetary policies using the interest rate instrument identified the news shocks less frequently than monetary policies using the monetary base instrument. Findings: The approximate value of the social loss function in the optimal commitment and discretionary monetary policies suggests that the optimal commitment policy is estimated to be lower in both cases. Due to value of the social loss function in optimal monetary policies with nominal interest rate instrument in the presence of news shocks, this could be claimed that monetary policy with interest rate instrument is more appropriate than the monetary policy with a monetary base instrument. Originality/value: The approximate value of the social loss function in the optimal commitment and discretionary monetary policies suggests that the optimal commitment policy is estimated to be lower in both cases.